A CPW-Fed Circular Microstrip Patch Antenna for UWB Applications (International Journal of Communication Systems and Network Technologies, 2023)
A design of circular microstrip patch antenna with CoplanarWaveguide (CPW) feeding for Ultra-Wide Band (UWB) applications has been presented. The proposed antenna is designed in CST simulation software for frequency range between 3.1 GHz and 10.6 GHz. The proposed antenna contains a circular radiation patch modified with a U-shape and an inverted U-shape slot and provided with CPW feeding for ease of integration with other microwave components. The antenna is of compact size 70 mm × 70 mm × 0.794 mm and obtains a maximum gain of 5.01 dBi and peak directivity of 7.58 dB at 8.72 GHz frequency. The antenna achieves a radiation efficiency of 99% and a VSWR of smaller than 2 across the UWB frequency range. Thus, the suggested antenna is suitable for UWB applications, offering a wide bandwidth, compact size, and stable radiation characteristics.
Keywords: Circular Microstrip Patch Antenna; CPW Fed; Ultra-wide Band; Gain; Directivity